WatAI: AI-Based System for Real-Time Flow Monitoring and Demand Prediction in Water Networks - Ladino-Moreno, E. O. (Civil Engineering Journal, 2025)
Efficient monitoring and control of water demand are crucial for sustainable water resource management. Bogotá, Colombia, currently faces supply rationing due to climate change and ineffective public policies. This study presents WatAI (Water + AI), an AI-powered system designed for real-time flow monitoring and demand prediction in water distribution networks. The system integrates flow sensors, microcontrollers, and machine learning algorithms to capture high-resolution temporal data. A dynamic sequential artificial neural network (ANN) with ReLU activation and Adam optimization is implemented, allowing real-time adjustments (1 sec) to flow variations and anomaly detection. To enhance accuracy, the system applies real-time signal filtering and transmits early alerts via email to service providers. The ANN model achieved an MSE of 0.006510, demonstrating improved accuracy with increasing historical data. Compared to traditional forecasting models, WatAI provides higher temporal resolution and adaptability to demand fluctuations, making it a more effective tool for intelligent water management. The study contributes to the development of IoT-based smart infrastructures for sustainable urban water planning.